Protection and economic value of estuary in central Gulf of Guinea: biodiversity and sustainable development. - (:unkn) unknown (My University, 2004)
The equatorial fringe of the gulf of Guinea represents an enormous floristic, fauna, and ecosystem wealth. Quite opposite to those of west Africa and Asia, they are enough well preserved, because of the weak human occupation. However, with the increase of the urban population, we can see a certain erosion of this biodiversity. While the first actions of these forests conservation and their fauna began about a century ago, important projects of conservation are being done for ten years and that the idea of an economic value for a lasting exploitation is starting to interest all the actors (explorers, conservators, local communities, political decision makers), new partnership actions proposed during the summit of sustainable development in Johannesburg in 2002 should be soon concretized. The protected areas, tools of conservation of the biodiversity are shown in Gabon and in Equatorial Guinea as well. Their openness to the ecotourism, on this coastal area of the Corisco bay is the object of this study.
Keywords: African Research